The ghosts of coloniality in the contemporary modern world - Mejía Navarrete, Julio (2020)
The text describes the development of coloniality in the modern contemporary world, from its dark side. Ghosts of coloniality that announce a dehumanized world, a future marked by the inferiorization of the majorities, the advent of a new xenophobicracial conflict, the emergence of «populist» and neo-fascist political forces, which involve the spread of a global project of cultural barbarism and a segregationist political regime.